Periinterventionelles Management der akuten endovaskulären Schlaganfallbehandlung - Schönenberger, Silvia; Bösel, Julian (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2019)
Mechanical thrombectomy (MT) is more effective than standard medical treatment with or without intravenous thrombolysis alone for treating acute ischemic stroke (AIS) caused by large vessel occlusion (LVO) in the anterior circulation. MT is therefore recommended in current international guidelines, and many acute-care hospitals and stroke centers will have to prepare for providing this treatment in an optimal way. Beside successful recanalization, management before, during, and after the intervention represents significant challenges. One unresolved matter is whether the choice of anesthetic strategy, including airway management, affects functional outcome. Based on current data, treatment under general anesthesia (GA)—respecting predefined safety criteria and contraindications—seem seems to be equivalent to treating the patient in conscious sedation (CS) and not necessarily disadvantageous. Aspects of periinterventional management of MT, including pragmatic recommendations concerning logistics, monitoring, postprocedural steps, and follow-up imaging, will be summarized in this overview.